Pengembangan Media Pembelajaran Berbasis Internet of Things Melalui Pendekatan STEM Investigative Science Learning Environment Untuk Meningkatkan Hasil Belajar Siswa - Abdul Hamid; Muhammad Syukri; A Halim; Irwansyah Irwansyah (Postgraduate, University of Mataram, 2022)
This study aims to design and implement IoT-based media using the STEM-based ISLE model to improve student learning outcomes. This type of research uses Research and Development with the Dick & Carrey development model. The products produced are teaching aids based on the Internet of Things (IoT), student worksheet, and lesson plan. The IoT-based teaching aids were developed using Long Range Area (LoRa) SX1276, Raspberry Pi 3 Model B+, Arduino Uno, and DHT11 sensors, the data is displayed on the ThingSpeak web which has been integrated with the TTN (The Things Network) web for analysis by students. The results of the validation of teaching aids by media experts showed an average value of 4.20, material experts got an average value of 4.16, and observer teachers 4.83 which showed that the teaching aids were feasible to be applied. Validation was also carried out on student worksheets and lesson plans, the average value of student worksheets validation by media experts showed a value of 4.75, while by material experts 3.99 and by teacher observers 5, therefore student worksheets were feasible to be applied in the learning process, as well as with lesson plans with a validation value of 4.33. The results of the pre and post-test student learning outcomes showed an increase in the completeness of 70%. These results indicate that IoT-based media and products developed are feasible to be applied and can improve student learning outcomes in the learning process.